Pararhigognostis—a new genus for Plutella stichocentra Meyrick, 1932 (Lepidoptera, Plutellidae), with a redescription of its male and female genitalia - Baraniak, Edward; Agassiz, David (Zootaxa, 2024)
Pararhigognostis Baraniak & Agassiz, gen. nov., is described and illustrated for the enigmatic Plutella stichocentra Meyrick, 1932. The morphology of male and female genitalia is described for the first time, and they serve to distinguish the new genus from all other genera of the family Plutellidae. The new genus is defined by the structure of the valva, long saccus, and shape of socii in the male genitalia, as well as by the shape of antrum and long, very thin apophyses posteriores in the female genitalia. The type species of Pararhigognostis, P. stichocentra, is redescribed. Line drawings of the male and female genitalia of the species are provided.